Branding: o poder simbólico das marcas - Zampieri, Lupércio (2022)
What are you going to eat? What clothes will you wear? How will you get around the city? With what will you quench your thirst? Routine consumer choices, which seem natural, gain new contours in contemporary times due to the economic and symbolic role that brands assume. This is a condition inherent to aesthetic capitalism, a scenario in which branding becomes central to companies' domination strategies and, consequently, a reason for disputes. Among these strategies, the British consulting company Interbrand stands out. It has created a method that gives economic value to brands, legitimized by the economic and business communication fields. In view of this, our study exposed the strategies and operations carried out by branding and its effects on the social world, in particular, how brands are used in the production of symbolic power; the symbolic efficacy of Interbrand's arbitrary method; and the contribution of branding to the economy of symbolic goods. In this sense, our research reported the structure of the global communication industry, its practices, capitals in dispute, the ideology of the "better world" that guides brands and how this discourse articulates with the neoliberal order